Tsw – A case study on structure-function puzzles in plant NLRs with unusually large LRR domains - van Grinsven, Irene Louise; Martin, Eliza C.; Petrescu, Andrei-José; Kormelink, Richard (Frontiers in Plant Science, 2022)
Plant disease immunity heavily depends on the recognition of plant pathogens and the subsequent activation of downstream immune pathways. Nod-like receptors are often crucial in this process. Tsw, a Nod-like resistance gene from Capsicum chinense conferring resistance against Tomato spotted wilt virus (TSWV), belongs to the small group of Nod-like receptors with unusually large LRR domains. While typical protein domain dimensions rarely exceed 500 amino acids due to stability constraints, the LRR of these unusual NLRs range from 1,000 to 3,400 amino acids and contain over 30 LRR repeats. The presence of such a multitude of repeats in one protein is also difficult to explain considering protein functionality. Interactions between the LRR and the other NLR domains (CC, TIR, NBS) take place within the first 10 LRR repeats, leaving the function of largest part of the LRR structure unexplained. Herein we discuss the structural modeling limits and various aspects of the structure-function relation conundrums of large LRRs focusing on Tsw, and raise questions regarding its recognition of its effector NSs and the possible inhibition on other domains as seen in other NLRs.